Penerapan Affixed Signature and Stamp pada Surat Keterangan Asal sebagai Mitigasi Kinerja Ekspor di Masa Pandemi Covid-19 - Ni Putu Ari Setiawati; I Wayan Sutrisna (Universitas Nusantara PGRI Kediri, 2024)
This research focuses on determining, implementing, factors that affect implementation and their implications for the export performance of Bali Province towards the G20 destination countries during the Covid-19 pandemic. The research method used is qualitative research. The informants used are from officials and exporters as policy implementers, as well as forwarders and carriers as implicated group targets. The questionnaire was distributed to 100 respondents, with 97 returned questionnaires. Based on the results of observations and interviews, it can be concluded that the establishment of the Regulation of the Minister of Trade of the Republic of Indonesia Number 39 of 2020 as a mitigation response in minimizing the impact of the Covid-19 pandemic in the smooth flow of goods in export performance. The Bali Provincial Industry and Trade Office as the Issuing Agency of Certificate of Origin (SKA) and exporters jointly implemented the Regulation of the Minister of Trade of the Republic of Indonesia Number 39 of 2020 by implementing the ASnS system in the original SKA issued, so that the efficiency of the SKA process can be improved, the smooth flow of goods can be increased, and export demand from G20 countries during the Covid-19 pandemic to Bali Province can be realized.